The principles of state and government in Islam - Asad, Muhammad (Malaysia, Islamic Book Trust, 1999)
The Principles of State and Government in Islam"" by Muhammad Asad is a comprehensive and insightful exploration of the Islamic principles of governance and politics. Asad, a renowned Islamic scholar and diplomat, draws on his extensive knowledge of Islamic history, law, and philosophy to provide a detailed analysis of the principles that underpin Islamic political thought.The book begins by examining the concept of the Islamic state and the role of the ruler in Islamic society. Asad argues that the Islamic state is not simply a political entity but also a moral and spiritual one, with the ruler serving as a guardian of the faith and a protector of the people. He goes on to explore the principles of justice, equality, and accountability that are central to Islamic governance, and the importance of consultation and consensus-building in decision-making.Asad also delves into the relationship between the state and the individual, discussing the rights and responsibilities of citizens in an Islamic society. He examines the role of the judiciary in upholding the rule of law, and the importance of education and cultural development in creating a just and harmonious society.Throughout the book, Asad draws on a wide range of Islamic sources, including the Qur'an, the Hadith, and the writings of Islamic scholars and philosophers. He also provides a critical analysis of modern political systems and their compatibility with Islamic principles.""The Principles of State and Government in Islam"" is an essential read for anyone interested in Islamic political thought and the principles of governance in Islamic societies. Asad's clear and insightful analysis provides a valuable resource for scholars, policymakers, and anyone seeking a deeper understanding of the Islamic approach to politics and governance.This scarce antiquarian book is a facsimile reprint of the old original and may contain some imperfections such as library marks and notations. Because we believe this work is culturally important, we have made it available as part of our commitment for protecting, preserving, and promoting the world's literature in affordable, high quality, modern editions, that are true to their original work.